Inhibition of BMP9 Induced Bone Formation by Salicylic-acid Polymer Capping. (2019) - Acri, Timothy M.; Laird, Noah Z.; Hong, Liu; Chakka, Jaidev L.; Shin, Kyungsup; Elangovan, Satheesh; Salem, Aliasger K.
Abstract: This work focuses on the development of a system to control the formation of bone to complement developments that have enabled potent regeneration of bony tissue. Scaffolds were fabricated with chemically modified RNA encoding for bone morphogenetic protein-9 (cmBMP9) and capped with salicylic acid (SA)-containing polymer (SAPAE). The goal was to determine if SAPAE could inhibit the formation of bone in a pilot animal study since cmBMP9 has been demonstrated to be highly effective in regenerating bone in a rat calvarial defect model. The results indicated that cmBMP9 increased bone formation (30% increase in area covered compared to control) and that SAPAE trended toward reducing the bone formation. These results suggest SAPAE could be useful as a chemical agent in reducing unwanted bone formation in implants loaded with cmBMP9.